The use of visualization of corporate data in strategic Information and Communications Technology industrialization - Dippenaar, Francois (Vaal University of Technology, 2013)
Global companies tend to have problems in knowing the systems, assets and resources they have within their global footprint. This tends to be costly to the company as there tends to be purchases of the same systems, assets and resources that are already available in another business unit or department within the company. This leads to money being wasted on research, procurement and/or training, to name a few. You can't manage what you don't know about. This thesis will show how the visualisation of corporate data is possible and has sustainable benefit to a company. Knowing the status of the Information and Communications Technology (ICT) environment in a company at some point in time is crucial in planning and implementing strategies with the future in mind. Global View, which will be explained in this thesis, is key in facilitating the extracting of information from all the sites globally and presenting the information in a logical and structured way. Information gathering from these sites using Global View needs to be done in an auditing fashion with the focus on accurate and precise information with an option which would allow the audit to be a continuous and automatic process. Global View is a tool to facilitate the implementation of ICT Industrialization through a process of gathering the relevant ICT information worldwide with specific reference to each site. Global View displays the relevant information from systems, assets, resources and environments in an easily accessible format. The functionality that is built into the concept in this thesis is the geographical and geospatial orientation which is linked to the relevant sites as well as time references related to Greenwich Mean Time to make users aware of differences in time when communicating with people in other countries either individually or multiple sites simultaneously.
M. Tech. (Department of Information and Communications Technology, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Visualization data; Corporate data; Strategic information; Industrialization; Information and Communication Technology (ICT); Global View; Dissertations, Academic -- South Africa.; Information technology.; Business communication.; Industrialization.; Management information systems.; Strategic planning.